2018
DOI: 10.1007/s10856-018-6116-7
|View full text |Cite
|
Sign up to set email alerts
|

Examination of 2-methacryloyloxyethyl phosphorylcholine polymer coated acrylic resin denture base material: surface characteristics and Candida albicans adhesion

Abstract: The aim of this study is to evaluate the effects of 2-methacryloyloxyethyl phosphorylcholine (MPC) polymer coating with various concentrations onto acrylic resin denture base material on surface characteristics such as contact angle and surface roughness and on Candida albicans adhesion which is the major factor of denture stomatitis. Specimens, prepared from heat-polymerized acrylic denture base material, were divided into control and three test groups, randomly. Surfaces of the specimens in test groups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
0
9
1
Order By: Relevance
“…16 This is assured by the correlation results of our study, which demonstrate a significant positive correlation between SR and candida adhesion. In contrast to this result, a previous study 39 found a slight rise in surface roughness values parallel to the increase in MPC polymer ratios.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…16 This is assured by the correlation results of our study, which demonstrate a significant positive correlation between SR and candida adhesion. In contrast to this result, a previous study 39 found a slight rise in surface roughness values parallel to the increase in MPC polymer ratios.…”
Section: Discussioncontrasting
confidence: 98%
“…Therefore, polyamide surface modification with MPC in a monomer density of 0.75 mol/L is suggested to be efficient, as it recorded decreased surface roughness and candida adhesion. While a previous study 39 recommended the MPC modification with 0.5 mol/ L concentration for coating acrylic denture base which recorded low candida adhesion with slight increase in surface roughness. This result can be explained by the difference in composition of both denture base materials.…”
Section: Discussionmentioning
confidence: 92%
“…Wettability was measured in accordance with the methods of previous studies [19,20]. Glycerol solution was chosen as the reference liquid, since it is an ideal blood analog with a similar viscosity to the normal range of human blood [19,21].…”
Section: Methodsmentioning
confidence: 99%
“…Applying the inclusion criteria, out of the 21 included articles,[ 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 ] 16 used surface coating, 4 added antimicrobial fillers, and 1 modified the chemical composition of PMMA (refer to Tables 2 and 3 for details). In addition to that, several included studies compared between smooth and rough surfaces of the modified specimens.…”
Section: R Esultsmentioning
confidence: 99%